Use of an Integrated Care Management Program to Uncover and Address Social Determinants of Health for Individuals With Lupus. Issue 5 (29th March 2021) - Taber, Kreager A.; Williams, Jessica N.; Huang, Weixing; McLaughlin, Katherine; Vogeli, Christine; Cunningham, Rebecca; Wichmann, Lisa; Feldman, Candace H.
Abstract : Objective: We studied patients with systemic lupus erythematosus (SLE) enrolled in a nurse‐led, multihospital, primary care–based integrated care management program (iCMP) for complex patients with chronic conditions to understand whether social determinants of health (SDoH), including food insecurity, housing instability, and financial constraints, were prevalent in this population. Methods: The academic hospital‐based iCMP enrolls the top 2% of medically and psychosocially complex patients identified on the basis of clinical complexity health care use, and primary care provider referral. A nurse conducts needs assessments and coordinates care. We reviewed the electronic medical records of enrolled patients with SLE to identify SDoH needs and corresponding actions taken 1 year prior to iCMP enrollment using physicians' and social workers' notes, and during enrollment using iCMP team members' notes. Results: Among 69 patients with SLE in the iCMP, in the year prior to enrollment, 57% had documentation of one or more SDoH challenges, compared with 94% during enrollment. iCMP nurses discussed and addressed one or more SDoH issues for 81% of the patients; transportation challenges, medication access, mental health care access, and financial insecurity were the most prevalent. Nurses connected 75% of these patients with related resources and support. Conclusion: Although SDoH‐related issues were not used to identify patients for the iCMP, the vast majority of enrolled medically and psychosocially complex patients with SLE had these needs. The iCMP team uncovered and addressed SDoH‐related concerns not documented prior to iCMP participation. Expansion of care management programs like the iCMP would help identify, document, and address these barriers that contribute to disparities in chronic disease care and outcomes.